Mercury concentrations in wild humpback whales (Megaptera novaeangliae) sampled in the Colombian Pacific and in Antarctic Peninsula - Angel Romero, Paula Andrea (Universidad de los Andes, 2017)
"The G stock of Humpback whales (Megaptera novaeangliae) conducts one of the longest cetacean migration from Antarctic Peninsula (feeding area) to the Southeast Pacific (breeding and calving area), being exposed to several pollutants such as mercury, which has been previously reported in the Antarctic. In order to assess the mercury concentration in skin and blubber of Humpback whales from the G stock, samples were collected in the Antarctic Peninsula (2015, n=15) and in the Colombian Pacific (Choco Province) (2015, n=14; 2016, n=42). Total mercury concentrations ([THg]) were measured by atomic absorption spectrometry (AMA-454, Altec). Results revealed significant differences in [THg] by tissue type in the same individual (n=22; p<0.05)." "El stock G de ballenas jorobadas (Megaptera novaeangliae) realiza una de las migraciones de cetáceos más largas desde la Península Antártica (área de alimentación) hacia el Pacífico sudeste (área de cría y parto), exponiendose a varios contaminantes como el mercurio, que se ha reportado anteriormente en el Antártico. Para evaluar la concentración de mercurio en la piel y la grasa de las ballenas jorobadas del stock G, se tomaron muestras en la Península Antártica (2015, n = 15) y en el Pacífico colombiano (Chocó) (2015, n = 14; 2016 , n = 42). Las concentraciones totales de mercurio ([THg]) se midieron mediante espectrometría de absorción atómica (AMA-454, Altec). Los resultados revelaron diferencias significativas en [THg] por tipo de tejido en el mismo individuo (n = 22; p<0.05)."Tomado del Formato de Documento de Grado Biólogo Pregrado